Using speech comprehension to qualify communication in classrooms: Influence of listening condition, task complexity and students' age and linguistic abilities. (November 2021) - Prodi, N.; Visentin, C.; Borella, E.; Mammarella, I.C.; Di Domenico, A.
Abstract: Oral communication is a fundamental part of teaching and learning in classrooms. Correct reception of the teacher's message is a necessary condition for good communication, though not sufficient to ensure that students will fully grasp its meaning. The traditional approach to the acoustic qualification of classrooms based on speech intelligibility alone might fail to capture the real impact of listening conditions on speech communication. A first aim of this study was to explore the use of a speech comprehension task combined with an assessment of listening effort as an alternative, more thorough way to qualify classroom acoustics. The speech comprehension task involved listening to sentences and was proposed to children aged 11–13 (N = 171). The test was administered collectively in the children's classroom in three different listening conditions. A second aim of the study was to use the speech comprehension test to investigate the impact of task difficulty, listening condition, and individual characteristics on speech communication. For this scope the task difficulty was manipulated by varying the syntactic complexity of the sentences. Data were acquired on both percentages of correct answers and response times, the latter being indicative of listening effort. With reference to the aims of the study, the results indicate that: (i) testing speech comprehension enables a comprehensive and ecological qualification of the impact of classroom acoustics on real-world listening abilities; and (ii) the effect of listening conditions on sentence comprehension is mediated by sentence complexity, and by listeners' age and linguistic abilities.